Copolymerization of aleuritic acid with l-lactic acid and study the aggregation behavior in different solvents - Pandey, Asutosh K.; Garnaik, Baijayantimala (International Journal of Research in Pharmacy and Chemistry, 2013)
In this present work, we highlight the copolymerization of L-lactic acid (L-LA with protected aleuritic acid in presence of Lewis acid catalyst using dehyropolycondensation method. The resulted copolymers are pliable, soft, waxy or even viscous liquid copolymers influenced by the aleuritic acid content. The purpose of this study is to investigate the physical properties. In addition, deprotected copolymers focus micelle-like aggregates in various organic solvents and mixed organic solvent at various proportions.